2017
DOI: 10.1002/2017ea000279
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in TRMM‐Era multisatellite‐based tropical rainfall estimates over the Maritime Continent

Abstract: This study investigates the regional and seasonal rainfall rate retrieval uncertainties within nine state‐of‐the‐art satellite‐based rainfall products over the Maritime Continent (MC) region. The results show consistently larger differences in mean daily rainfall among products over land, especially over mountains and along coasts, compared to over ocean, by about 20% for low to medium rain rates and 5% for heavy rain rates. However, rainfall differences among the products do not exhibit any seasonal dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 71 publications
(129 reference statements)
4
44
0
Order By: Relevance
“…A spectral analysis of the merged δ 18 O time series demonstrates a dominant cycle spanning a period of between 10 and 70 days (Figure ). This is consistent with the pronounced ISV modes of Sarawak rainfall, which span periods of 20 to 90 days (Kanamori, Yasunari, & Kuraji, ; Rauniyar et al., ). Moerman et al () also found that the day‐to‐day δ 18 O variability was correlated more strongly with the TRMM rainfall retrieved within the 2.5° × 2.5° longitude/latitude box than with the local precipitation.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…A spectral analysis of the merged δ 18 O time series demonstrates a dominant cycle spanning a period of between 10 and 70 days (Figure ). This is consistent with the pronounced ISV modes of Sarawak rainfall, which span periods of 20 to 90 days (Kanamori, Yasunari, & Kuraji, ; Rauniyar et al., ). Moerman et al () also found that the day‐to‐day δ 18 O variability was correlated more strongly with the TRMM rainfall retrieved within the 2.5° × 2.5° longitude/latitude box than with the local precipitation.…”
Section: Resultssupporting
confidence: 83%
“…Original data are available online at http://disc.gsfc.nasa.gov/datacollection/TRMM_3B42_V7.shtml. At daily or longer time scale, the TRMM 3B42 has been found to moderately reproduce observed area averaged precipitation over Sarawak region (Rauniyar, Protat, & Kanamori, ).…”
Section: Methodsmentioning
confidence: 96%
“…These spatial and temporal resolutions are higher than most available precipitation products and CHIRPS data have been used by previous studies focusing on the MCR (Hermawan et al ., ; Rustiana et al ., ). While recent comparisons indicate that no single dataset is coherently better in all of the precipitation parameters analyzed (Rauniyar et al ., ), CHIRPS outperforms other datasets at the seasonal scale and offers the best spatial distribution of daily values. We believe CHIRPS data provide the best estimates of observed rainfall for the goals of this project.…”
Section: Methodsmentioning
confidence: 99%
“…A key advantage of FIGGRA is a quantitative analysis of heterogeneities under nonstationarities based on systematic classification. Due to this advantage, FIGGRA may be an advanced and reliable alternative algorithm for Earth imagery classification and the associated diverse studies or practices [Jiang and Shekhar, 2017;Rauniyar et al, 2017;Schwenk et al, 2017]. In addition, FIGGRA-based spatial/temporal heterogeneity analysis may facilitate improvement of various quantitative analysis approaches for investigating many problems in Earth and space sciences, e.g., monitoring network design [Mishra et al, 2016;Gleason et al, 2017], urban ecology [Bardhan et al, 2016], representative-days selection [Rife et al, 2013], O 3 distribution detection [Parrish et al, 2016], spatial tracking or navigation [Fuchs et al, 2015;Palmer et al, 2016], tsunamis modeling [Grawe and Makela, 2015], atmospheric process analyses [Weisz et al, 2015], seafloor venting detection [Smart et al, 2017], sporadic E propagation [Ghosh and Berkey, 2015], or eco-system analysis [Zhang et al, 2017].…”
Section: Potential Extensionsmentioning
confidence: 99%